Diagnostic challenge in parathyroid carcinoma with multiple pathological bone fracture: A case report - Hermin Aminah Usman; Hasrayati Agustina; Zahra Nurusshofa; Siska Dwiyantie Wahyuni (Faculty of Medicine, Universitas Islam Indonesia, 2020)
Parathyroid carcinoma is a rare cause of primary hyperparathyroidism. It often presents with unspecified clinical manifestation that leads to misdiagnosis. We report a case of a 36-year-old woman who suffered from multiple bone tumours and recurrent bone fracture for 3 years ago, and misdiagnosis as only a giant cell tumours of the bone. Then, the patient continued to develop another mass in the neck that kept growing and the mass move on swallowing. The clinician diagnosed her as a colloid goitre based on cytological examination from fine-needle aspiration biopsy. Elevated parathyroid hormone level, hypercalcemia, and suspected parathyroid adenoma in the Sestamibi Parathyroid scan led the clinician to perform a frozen section in this patient with subsequent histopathological of diagnosis as parathyroid carcinoma. The diagnosis of parathyroid carcinoma continues to be a challenge. Understanding the pathogenesis and multidisciplinary collaboration is important to define an accurate diagnosis and treatment.